Does size matter? Implications of household size for economic growth and convergence - Vadim Kufenko; Vincent Geloso; Klaus Prettner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2018)
We assess the effects of changes in household size on the long-run evolution of living standards and on cross-country convergence. When the observed changes in average household size across countries are taken into consideration, growth in living standards is slower throughout the 20th century as compared to a measure based on per capita GDP. Furthermore, the speed of divergence between different countries before 1950 is faster and the speed of convergence after 1950 is slower after adjusting for the evolution in household size.
urn:nbn:de:bsz:100-opus-14743
Keywords: J11; O11; O47; 330; divergence; convergence; long-run growth; changing household size; demography